The BFG - Dahl, Roald, 1916-1990. (London : Heinemann, 1982)
Kidsnecched from her orphanege by a BFG (Big Friendly Giant) who spends his life blowing happy dreams to children, Sophie concocts a plan with him to save the world from nine other man-gobbling cannybull giants.
Keywords: Giants -- Fiction; Orphans -- Fiction